HTC167: Commercial Cookery / Faculty of Hotel & Tourism Management - UiTM, Faculty of Hotel and Tourism Management (2023)
Students will be introduced towards the attainment of knowledge through hands-on practice in food preparation to complement the Basic Table Service in the subject of Food and Beverage Service I. Production of menu reflecting influences of Western and Eastern. The production will also focus on different methods of cooking such as grilling, baking, roasting, stewing, braising and other methods of cooking. This course also designed in such way that it corresponds to the skill development for a more profound understanding of food and cooking. The practicality is on developing knowledge, food presentation skills and product development.